Politicizations of a Sacred River: The Story of Gaumukh-Uttarkashi Eco-Sensitive Zone, Uttarakhand, India - Lafaye de Micheaux, Flore (Journal for the study of religion, nature and culture, 2019)
The Gaumukh-Uttarkashi Eco-Sensitive Zone (ESZ) conservation perimeter in the Himalayan Garhwal region was gazetted in December 2012. However, this was only one moment in a tense and twisted political process, which began in 2004, between pro-dam and anti-dam coalitions. The sacredness of this holy source of the Ganges played a role in the political fate of this decision, along with conflicting perspectives defended by hydropower proponents versus environmentalists or state versus central governments. Some of the actors' motivations and political strategies derived from the formulation of a different ontology of the river, in which the river and humans are intrinsically connected or share an internal relation. The effects of this mobilization were volatile in the ESZ process but the ontological dimension of the conflict has had ramifications on later politics and policies. This case highlights the interest of bringing insights from political ontology into the political ecology of water.